Reducing the Global Burden of Cardiovascular Disease, Part 2: Prevention and Treatment of Cardiovascular Disease - Leong, Darryl P; Joseph, Philip G; McKee, Martin; Anand, Sonia S; Teo, Koon K; Schwalm, Jon-David; Yusuf, Salim (Circulation research, 2017)
In this second part of a 2-part series on the global burden of cardiovascular disease, we review the proven, effective approaches to the prevention and treatment of cardiovascular disease. We specifically review the management of acute cardiovascular diseases, including acute coronary syndromes and stroke; the care of cardiovascular disease in the ambulatory setting, including medical strategies for vascular disease, atrial fibrillation, and heart failure; surgical strategies for arterial revascularization, rheumatic and other valvular heart disease, and symptomatic bradyarrhythmia; and approaches to the prevention of cardiovascular disease, including lifestyle factors, blood pressure control, cholesterol-lowering, antithrombotic therapy, and fixed-dose combination therapy. We also discuss cardiovascular disease prevention in diabetes mellitus; digital health interventions; the importance of socioeconomic status and universal health coverage. We review building capacity for conduction cardiovascular intervention through strengthening healthcare systems, priority setting, and the role of cost effectiveness.